Granulomatous amoebic encephalitis in an immunocompetent young female: A rare case with microbiological confirmation and survival (Indian Journal of Case Reports, 2025)
Granulomatous amoebic encephalitis (GAE) is an uncommon but life-threatening central nervous system infection caused by Acanthamoeba species. It predominantly affects immunocompromised individuals, although cases in immunocompetent hosts are increasingly reported. We present the case of a 23-year-old previously healthy female who developed fever, severe headache, diplopia, vomiting, and altered sensorium. Magnetic resonance imaging showed mild cerebral atrophy, and cerebrospinal fluid (CSF) analysis revealed markedly elevated leukocyte count with mildly raised protein. CSF wet mount and Giemsa stain demonstrated trophozoites of Acanthamoeba with acanthopodia. Culture and other routine CSF tests were negative. The patient was treated with a combination of fluconazole, cotrimoxazole, rifampicin, and miltefosine and showed a significant improvement. She was discharged in stable condition. This case underscores the importance of clinical suspicion, timely diagnosis using microscopy, and the effectiveness of multidrug therapy in managing this otherwise fatal condition.